Latent error detection during in-situ simulation training in a district general hospital. (24th May 2012) - Yajamanyam, P K; Sohi, D; King, S; Wilkey, O; Sinclair, H
Abstract : Aim: To evaluate the benefit of in-situ simulation in detecting latent errors and improving patient safety in a district general hospital in London. Methodology: Weekly in-situ simulation training was conducted within the paediatric A+E and the neonatal unit from February 2011. Structured scenarios were used with predetermined learning objectives. Training was jointly delivered by a consultant paediatrician trained in paediatric simulation, a resuscitation officer and a medical education fellow. Debrief sessions were facilitated at the end of each scenario involving the whole team. Low fidelity simulation was conducted for the first 8 months, with addition of high fidelity baby and neonatal simulators in the last 2 months. Outcomes included trainee feedback and reflective notes and identification of any clinical governance issues. Results: Information on latent errors identified was available from 20 paediatric and 8 neonatal sessions out of 40 sessions. A total of 6 (6/40) latent errors were identified with no latent errors detected in the rest of the sessions (34/40). These were classified according to the NPSA guidance on risk assessment (table 1 ) with the help of local risk management team. All errors were recorded through the trust's incident reporting system and necessary actions were undertaken immediately. Conclusions: We conclude that in-situ simulation is an effective way of detecting latent errors without compromising patient safety. We recommend that identified errors should be reported using local incident reporting system to rectify the situation. Providing high fidelity in-situ simulation is resource intensive for any NHS trust. We have been able to demonstrate that, using low fidelity simulation equipment available in most resuscitation departments in district general hospitals, effective in-situ simulation can be conducted to improve training and patient safety. In the future we aim to compare high fidelity to low fidelity in-situ simulation in detecting latent errors.